2018
DOI: 10.3390/ijerph15081730
|View full text |Cite
|
Sign up to set email alerts
|

How Would Economic Development Influence Carbon Productivity? A Case from Hubei in China

Abstract: Carbon productivity, defined as the gross domestic product (GDP) per unit of CO2 emissions, has been used by provincial governments in China as in indicator for effort and effect in addressing climate-change problems. The aggregate impact of economic growth on carbon productivity is complex and worthy of extensive investigation to design effective environmental and economic policies. Based on a novel combination of the smooth transition regression model and the Markov regime-switching regression model, this pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…However, in the study of Hu and Wang (2020) [43], appropriate regulatory policies had obvious effects on carbon productivity. In addition, Wang et al (2018) [44] regarded economic growth as a crucial factor based on a time series model, and Li and Wang (2019) [45] explored the improvement plan of carbon productivity from the perspective of a socio-economic development strategy. (3) The relationship between industrial upgrading and carbon productivity-related indicators.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, in the study of Hu and Wang (2020) [43], appropriate regulatory policies had obvious effects on carbon productivity. In addition, Wang et al (2018) [44] regarded economic growth as a crucial factor based on a time series model, and Li and Wang (2019) [45] explored the improvement plan of carbon productivity from the perspective of a socio-economic development strategy. (3) The relationship between industrial upgrading and carbon productivity-related indicators.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Secondly, research has concentrated on exploring the factors affecting CP. Previous studies have primarily focused on industrial structure [37,38], technological progress [39][40][41][42], the degree of trade openness [43,44], economic development [45,46], energy structure [47,48], and other aspects.…”
Section: Carbon Productivitymentioning
confidence: 99%
“…From a socio-economic development perspective, it is a challenge to promote carbon reduction and economic growth at the same time. Wang et al ( 2018 ) and Li and Wang ( 2019 ) showed that economic growth promoted carbon productivity and there was a non-linear relationship. Environmental regulation is an important tool for government environmental management.…”
Section: Literature Reviewmentioning
confidence: 99%